Kulturno-duhovno okolje, iz katerega je izšel dr. Vekoslav Grmič - Čuš, Franc (Časopis za zgodovino in narodopisje, 2023)
The cultural, religious, educational, economic, ethnic, and political elements that influenced the rich intellectual potential of the environment in which he was born, grew up, and kept returning to are beeing introduced.
Keywords: biografije; domoznanstvo; Dragotinci; Grmič, Vekoslav; Prleške Atene; versko življenje